Roh Kudus Era Digital: Telaah Pneumatologis terhadap Kecerdasan Buatan (AI) dalam Liturgi Virtual - Telaumbanua, Agus Arda Setiawan (Sekolah Tinggi Teologi Baptis Indonesia, 2025)
The advancement of digital technology, particularly artificial intelligence (AI), has brought significant changes to Christian liturgical practices. Worship, which was once physical in nature, is now also conducted virtually through digital platforms, even involving AI as a technical support tool in liturgy. This shift raises a critical theological question: can the Holy Spirit be present and work through artificial intelligence, which is non-personal and programmed, within digital liturgy? This article aims to critically examine this issue through a pneumatological approach. The study employs a qualitative method using a literature review. The findings indicate that although AI can assist in technical aspects of worship such as composing sermons, prayers, or liturgical content AI does not possess spiritual attributes, consciousness, or will as the Holy Spirit does. The Holy Spirit is a Divine Person who works personally and transcendentally within the community of faith. His presence cannot be replaced by digital systems or algorithmic media that are impersonal in nature. In conclusion, AI can function only as a technical tool in worship but cannot serve as a medium for the Holy Spirit’s presence. The Church must develop the use of technology wisely and theologically, so as not to obscure the role of the Holy Spirit in worship, and to preserve the authenticity of spirituality and the faith community in the face of digital transformation. Therefore, this study contributes to the discourse of digital theology and contemporary pneumatology by highlighting the ontological and theological limitations of AI in the context of divine presence, while also expanding interdisciplinary discussions between technology, liturgy, and the presence of the Holy Spirit in increasingly digital worship spaces